2020
DOI: 10.1016/j.diabres.2020.108312
|View full text |Cite
|
Sign up to set email alerts
|

Association of mental disorders and quality of diabetes care – A six-year follow-up study of type 2 diabetes patients in North Karelia, Finland

Abstract: To compare the quality of diabetes care among type 2 diabetes patients with and without mental disorders during six-year follow-up in North Karelia, Finland. Methods: All type 2 diabetes patients (n = 10190) were analysed using the electronic health records data from 2011-12 to 2015-16. The diabetes care was evaluated using the measurement activity and the achievement of the treatment targets for HbA1c and LDL. Results: Monitoring of HbA1c and LDL levels improved among all patient groups, except the dementia p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 39 publications
0
5
0
1
Order By: Relevance
“…The results of these studies and reasons for exclusion are summarised in Table . Out of these thirteen studies, five reported that major depressive disorder/higher levels of depressive symptoms were longitudinally associated with higher levels of HbA 1c, 26,28–30,36 while eight did not find an association 22,25,27,32–35,47 . One study described their results without reporting an effect estimate 47 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The results of these studies and reasons for exclusion are summarised in Table . Out of these thirteen studies, five reported that major depressive disorder/higher levels of depressive symptoms were longitudinally associated with higher levels of HbA 1c, 26,28–30,36 while eight did not find an association 22,25,27,32–35,47 . One study described their results without reporting an effect estimate 47 …”
Section: Resultsmentioning
confidence: 99%
“…The results of 11 studies could be subjected to meta‐analysis. Fifteen studies 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 had to be excluded from the meta‐analysis as the reported effect measures could not be pooled in a meta‐analysis. The exact reasons for exclusion can be found in Tables S5 and S6 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…57 Moreover, the psychological status of pregnant women also has a certain impact on maternal and offspring outcomes. 55,58,59 Evidence suggests that strategies to tailor psychological interventions modules based on smartphone help adults with diabetes cope positively and achieve diabetes treatment goals. 60 Therefore, psychological intervention elements must be integrated into smartphone-based lifestyle interventions to investigate the effects on psychological status among women with GDM in future studies.…”
Section: Discussionmentioning
confidence: 99%